Cutting edge of genetically modified pigs targeting complement activation for xenotransplantation - Sun, Qin; Song, Si-Yuan; Ma, Jiabao; Li, Danni; Wang, Yiping; Yang, Zhengteng; Wang, Yi (Frontiers in Immunology, 2024)
In the quest to address the critical shortage of donor organs for transplantation, xenotransplantation stands out as a promising solution, offering a more abundant supply of donor organs. Yet, its widespread clinical adoption remains hindered by significant challenges, chief among them being immunological rejection.Central to this issue is the role of the complement system, an essential component of innate immunity that frequently triggers acute and chronic rejection through hyperacute immune responses. Such responses can rapidly lead to transplant embolism, compromising the function of the transplanted organ and ultimately causing graft failure. This review delves into three key areas of xenotransplantation research. It begins by examining the mechanisms through which xenotransplantation activates both the classical and alternative complement pathways. It then assesses the current landscape of xenotransplantation from donor pigs, with a particular emphasis on the innovative strides made in genetically engineering pigs to evade complement system activation. These modifications are critical in mitigating the discordance between pig endogenous retroviruses and human immune molecules. Additionally, the review discusses pharmacological interventions designed to support transplantation. By exploring the intricate relationship between the complement system and xenotransplantation, this retrospective analysis not only underscores the scientific and clinical importance of this field but also sheds light on the potential pathways to overcoming one of the major barriers to the success of xenografts. As such, the insights offered here hold significant promise for advancing xenotransplantation from a research concept to a viable clinical reality.